2017
DOI: 10.1136/heartjnl-2017-311944
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of an acoustic-based system for coronary artery disease risk stratification

Abstract: ObjectiveDiagnosing coronary artery disease (CAD) continues to require substantial healthcare resources. Acoustic analysis of transcutaneous heart sounds of cardiac movement and intracoronary turbulence due to obstructive coronary disease could potentially change this. The aim of this study was thus to test the diagnostic accuracy of a new portable acoustic device for detection of CAD.MethodsWe included 1675 patients consecutively with low to intermediate likelihood of CAD who had been referred for cardiac CT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
64
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(74 citation statements)
references
References 17 publications
9
64
1
Order By: Relevance
“…For detection of stable coronary artery disease (CAD), patients undergo risk stratification, non-invasive and invasive testing [1]. However, recent studies have demonstrated that as low as 6–10% of patients referred to non-invasive testing suffer from significant CAD [24]. A safe and low-cost rule-out test reducing the number of patients with non-obstructive CAD referred to non-invasive testing could therefore reduce costs and potential risk of complications.…”
Section: Introductionmentioning
confidence: 99%
“…For detection of stable coronary artery disease (CAD), patients undergo risk stratification, non-invasive and invasive testing [1]. However, recent studies have demonstrated that as low as 6–10% of patients referred to non-invasive testing suffer from significant CAD [24]. A safe and low-cost rule-out test reducing the number of patients with non-obstructive CAD referred to non-invasive testing could therefore reduce costs and potential risk of complications.…”
Section: Introductionmentioning
confidence: 99%
“…To lower the overall mortality rate of CAD, a technology is required, which is inexpensive, easy to use, fast, reliable and accurate. As a result, a great interest in alternative techniques has been promoted to simplify the procedure of detecting CAD (for example recently a method has been suggested for detecting CAD using the sound of turbulent blood flow induced by coronary stenosis Schmidt et al, 2015; Winther et al, 2016, 2018; Thomas et al, 2017). Among them a technology using seismocardiography (SCG) for detecting CAD has the potential to fulfill these requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Phonocardiography recordings were pooled from three different studies: AdoptCAD [5], BIO-CAC (NCT02913144), and Dan-NICAD [6,7] as shown in Table 1. Only one recording for each subject was included; in cases where more than one recording were available, the first recording was selected.…”
Section: Datamentioning
confidence: 99%